PPARgamma-Dependent Control of Renin Expression: Molecular Mechanisms and Pathophysiological Relevance. (30th October 2013) - Todorov, Vladimir T.
Abstract : During the last years accumulating evidence demonstrated that the nuclear receptor peroxisome proliferator-activated receptor-gamma (PPARgamma) regulates the expression of renin gene and thus the overall renin production. This review summarizes the current knowledge of the transcriptional control of the renin gene by PPARgamma received from variety of models ranging from cell culture to transgenic animals. The molecular mechanisms of the PPARgamma action on renin are particularly interesting because they are featured by two newly described characteristics: one of them is the recently identified PPARgamma target sequence Pal3 which is specific for the human renin gene and mediates exceptionally high sensitivity to transactivation; the other is the potentiating effect of PPARgamma on the cAMP signaling in the renin-producing cells. Furthermore, I discuss the need for generating of additional transgenic animal models which are more appropriate with regard to the role of the PPARgamma-dependent regulation of the renin gene expression in human diseases such as arterial hypertension and metabolic syndrome.